1998
DOI: 10.1161/01.atv.18.5.723
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Cell Adhesion Molecules in Hypertriglyceridemia and Potential Significance on Monocyte Adhesion

Abstract: Abstract-Hypertriglyceridemia may contribute to the development of atherosclerosis by increasing expression of cell adhesion molecules (CAMs). Although the cellular expression of CAMs is difficult to assess clinically, soluble forms of CAMs (sCAMs) are present in the circulation and may serve as markers for CAMs. In this study, we examined the association between sCAMs and other risk factors occurring with hypertriglyceridemia, the effect of triglyceride reduction on sCAM levels, and the role of soluble vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
146
7
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(165 citation statements)
references
References 44 publications
9
146
7
3
Order By: Relevance
“…02), and soluble E selectin (P = 0 . 0001), but did not change soluble VCAM-1 concentration (61) . In another study with type 2 diabetic patients, EPA (1 .…”
Section: N-3 Pufa and Adhesion Moleculesmentioning
confidence: 79%
“…02), and soluble E selectin (P = 0 . 0001), but did not change soluble VCAM-1 concentration (61) . In another study with type 2 diabetic patients, EPA (1 .…”
Section: N-3 Pufa and Adhesion Moleculesmentioning
confidence: 79%
“…Oxidative stress may also play a pathophysiological role in the endothelial dysfunction in first-degree relatives (18), although we did not measure parameters of it. On the other hand, it could be argued that the increase in sICAM-1, which is a marker of endothelial cell activation (7), could be secondary to subclinical CVD in first-degree relatives, a possibility consistent with evidence that concentrations of sICAM-1 are correlated with the degree of intima-media thickness (19), which is increased in first-degree relatives (20). Our study was not designed to compare the value of FMD and CFVR as early markers of cardiovascular risk in firstdegree relatives.…”
Section: Conclusion -Prior Et Al (13)mentioning
confidence: 87%
“…The expression of E-selectin, ICAM-1 and VCAM-1is relatively low in normal vascular cells and is upregulated in response to various stimuli, including cytokines and oxidants, thus enabling monocytes to adhere to the vessel wall. In vivo animal studies and immunohistochemical studies of human tissues have shown that these CAMs are expressed at increased levels in atherosclerotic plaques (47). The normal endothelium is characterized by the production of a number of molecules that affect the contractile state of adjacent myocytes and the behavior of formed elements within the blood stream, and by the absence of cell surface adhesion molecules.…”
Section: Increase Of Endothelial Expression Of Cell Adhesion Moleculesmentioning
confidence: 99%